The Effect of Orientation Strategy on Logistics Performance with Supply Chain Integration as a Mediation Variable - Ikanita Novirina Sulistyari; Fuad Mas’ud (Syntax Idea)
Ports have a big role in the logistics system. Because at the port various logistics activities occur such as transportation activities, loading, and unloading of goods, inspection, storage, and so on. So the performance of the port plays an important role in the speed of delivery of logistics goods. Furthermore, for the transportation of logistics goods, trucking is one of the options that can be chosen to deliver goods from the port to the customer. The process of shipping logistics goods by trucking begins with the pick-up of goods at the port by a predetermined truck. After that, the truck will take the goods to the destination address specified by the customer. This study aims to examine how the influence of supply chain orientation on logistics performance through supply chain integration as an intervening variable, a research study was conducted on manufacturing companies engaged in consumer goods processing services that use coal transportation services. The research method used in this study is quantitative using data collection techniques, observation, surveys, and primary data analysis. The survey is conducted by giving questionnaires or interviews to respondents to collect data on the variables studied. The research sample was 135 samples as owners or managers in manufacturing companies engaged in consumer goods processing services that use goods transportation services at the port of Central Java. Research analysis tools using AMOS 22.00 software with the SEM (Structural Equation Modeling) method. The results showed that there was a significant influence of supply chain orientation on logistics performance with a p-value of 0.036 and a CR value of 2.092 (can receive H1). There is a significant positive influence of supply chain orientation on supply chain integration with a p-value of 0.009 and a CR value of 2.625 (can accept H2). There is a significant effect of supply chain integration on logistics performance with a p-value of 0.015 and a CR value of 2.441 (can accept H3).